ANALISIS HUBUNGAN SALURAN TEGANGAN TINGGI LISTRIK TERHADAP JARINGAN SELULAR DI DAERAH GRAHA INDAH TAMBAKBOYO LAMONGAN - Kemal Farouq Mauladi; Nurul Fuad (Universitas Islam Lamongan, 2019)
Telecommunications technology is developing very rapidly, ranging from users or engineers. The development of smartphone smartphones is also increasingly in demand, so that the use of electricity needs is also increasing. The need for electricity usage has resulted in more standing voltage in some settlements. The establishment of sutet will have a negative impact on public health. In addition, the influence of electrical energy on humans occurs because the electrical energy generated by electricity generation or electricity that is channeled gives rise to electromagnetic fields. The higher the voltage required by an equipment, the greater the electric field that is distributed. Besides that, it can also find ways to reduce the negative impact of the electric and magnetic fields produced by SUTET which impacts the process of the occurrence of electric and magnetic fields on SUTET. From the problems above, the author intends to determine the effect or correlation between the impact of SUTET on cellphone network transmissions or channels. This research can later determine the negative impact caused by SUTET for the surrounding community, and the impact of SUTET radiation on cellular networks.